USE OF FMEA METHOD IN MANUFACTURE OF CABINET FURNITURE TO INCREASE QUALITY - Mihajlova, Julia; Mladenova, Diyana; Mladenova, Diyana (Innovation in Woodworking Industry and Engineering design, 2012)
Quality of products manufactured takes an extremely important position in all types of manufacture today. This is necessitated by the continuously growing competition at market level – customers value more and more quality products and turn to those companies that can give them the necessary thing according to their requirements. This applies especially to furniture-manufacturing companies. That is why of extreme importance is to find the exact approaches and methods for quality management and assurance. One of those methods is the FMEA (Failure Mode and Effect Analysis) method that is an analytical engineering method used to examine and eliminate potential discrepancies, problems, faults and errors. The aim of the paper is to establish the possibility of application of the FMEA method in increasing the quality of cabinet furniture manufactured, with following tasks having been carried out: an assessment of the risk of allowing potential discrepancies, problems, faults and errors during manufacture of cabinet furniture in specific company has been performed, by characterising the reasons leading to them by means of application of the FMEA method; the necessary actions for improvement have been determined; a new assessment of the risk of potential discrepancies, problems, faults and errors after performance of the outlined improvements by means of the FMEA method has been made.